Efektivitas Media Visual Baliho pada Program Lapor Pak Kapolsek - Rahmawati, Rifka Amelia; Yusuf, Eka; Ema (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
A communication must consider the way the message is conveyed so that it is easily understood, accepted and attracts public attention in increasing public trust. Cikampek Police recently launched an innovative program, the 'Report the Police Chief' program. This program was designed in an effort to shape the implementation of Precision Police and open up space for police communication with the community. In this program, the Cikampek Police are assisted by the media in carrying out socialization, namely the Billboard media. For this reason, it is currently considered effective if seen from the perspective of society, namely heterogeneous, that is, divided into various groups such as people who live and carry out activities in the jurisdiction of the Cikampek Police. This research uses the S-O-R Theory by Hovland and uses a quantitative approach. The population in this study were people in the jurisdiction of the Cikampek Police, with a sample of 90 people who met the age limit criteria of 17-45 years. The results of this research concluded that there was an influence on the effectiveness of the Report Mr. Police Chief billboard media on the attitudes of the community in the jurisdiction of the Cikampek Police, which was proven by the results of the T Test or Hypothesis which showed a significance result of 0.001 < 0.05 with a calculated T value of 17.691 > T Table 1.986